Weeds and their responses to management efforts in a changing climate - Anwar, Md. Parvez; Islam, A. K. M. Mominul; Yeasmin, Sabina; Rashid, Md. Harun; Juraimi, Abdul Shukor; Ahmed, Sharif; Shrestha, Anil (MDPI, 2021)
Crop production is a constant battle with weeds, in which weeds, generally, are victorious. Therefore, rather than channeling our efforts into the development of a “silver bullet” to control weeds, the focus should be on sustainable weed management in both natural- and agro-ecosystems. However, sustainable weed management can be a challenge in the context of global climate change. Over the past few decades, global climate change, mostly indicated by phenomena such as increased atmospheric temperature and elevated CO2 levels, is evident due to human activities and natural events. These phenomena also affect regional/local climate, resulting in significant influences on the agricultural systems of a particular region. Rising CO2 levels may give comparative advantages to C3 plants through increased photosynthesis, biomass production and yield, compared to C4 plants. Plants with C4 photosynthetic pathways, on the other hand, are likely to benefit more from rising global temperatures than C3 plants. Thus, the differential responses of C3 and C4 plants to climate change may alter crop–weed interactions and competition outcomes, most likely at the expense of the crop. Climate change will likely cause shifts in weed community compositions, their population dynamics, life cycle, phenology, and infestation pressure. Some weed species may go extinct, while some others may become more aggressive invaders. Weeds are, generally, colonizers and have some unique biological traits and ecological amplitudes that enable them to successfully dominate crops in a habitat with changed environmental conditions. Moreover, climate shifts, especially erratic rainfall and drought, may affect herbicide selectivity and efficacy or the success of bio-control agents resulting in an establishment of a mixed and complex population of C3 and C4 weed species adding to the complexity of weed management. Although elevated CO2 levels will stimulate the productivity of major C3 crops, most troublesome agricultural weeds will likely be more responsive to a rise in CO2 than crops, and thus may dominate the agro-ecosystem. It is predicted that, as temperature rises, the majority of the C4 weeds will flourish and will pose serious crop yield losses. Understanding and assessment of the impact of simultaneous changes in multiple climate factors and their complex interactions on crops and weeds are therefore necessary to formulate an adaptive weed management approach and build resilience. Moreover, strategic policies and strong actions need to be taken to reduce the root causes of CO2 and other greenhouse gas emissions to minimize the impact of climate change on weed biology and management.